How moral outrage affects consumer's perceived values of socially irresponsible companies - Manuela Escobar-Sierra; Alejandra García Cardona; Luz Dinora Vera Acevedo (Cogent Business & Management, 2021)
The research about responsible consumption began during the 70's decade, but recently it became extremely relevant due to global warming and increasing social demands. In this regard, our research tries to determine the effects of moral outrage on consumers' perceived values of socially irresponsible companies. Once we introduce our research problem, we conduct in the first stage a literature review, to construct a conceptual model for responsible consumption. In the second section, we verified our previous conceptual model at a practical level, applying a quantitative approach through structural equations. Specifically, we verify the effects of the moral outrage, on consumers' perceived values, in the context of a price cartel, that operated for more than 14 years, involving the biggest five producers of toilet paper, napkins, diapers, and handkerchiefs in Colombia. The findings show that the moral outrage due to corporate social irresponsibility, affect the consumer's perceived values, related to (i) the consumer loyalty, and (ii) the consumer social and economic costs. Based on these findings, we suggest some implications for marketing practitioners, public policy-makers, shareholders and CEOs. Furthermore, we also recommend the future inclusion of the control mechanisms, and the technical cycle for products and services, in the responsible consumption studies.
Keywords: M14; M38; N16; D73; 650; responsible consumption; corporate social irresponsibility; moral outrage; consumers' perceived values; structural equations modelling SEM